Systemic Manifestations, Tooth Eruption and Enamel Defects in Children with Congenital Zika Virus Syndrome: 36-Month Follow-up Case Series - Alidianne Fábia Cabral Cavalcanti; Taynná Dantas de Arruda; Yeska Paola Costa Aguiar; Adriana Suely de Oliveira Melo; Jeime Iara Bezerra de Freitas Leal; Emna Hidoussi Sakly; Myroslav Goncharuk-Khomyn; Sérgio D'Avila Lins Bezerra Cavalcanti; Alessandro Leite Cavalcanti (Association of Support to Oral Health Research (APESB), 2022)
Objective: To describe systemic manifestations, the characteristics related to tooth eruption, and the occurrence of enamel defects in children with Congenital Zika Virus Syndrome (CZS). Material and Methods: Prospective case series based on nine children with confirmed CZS diagnosis assisted at a reference center in a municipality in the Northeast Region of Brazil. Through a structured interview directed to mothers, information related to prenatal, delivery, and postpartum periods was collected. Tooth eruption was monitored through clinical examinations for 36 months. The modified developmental defect of enamel index (DDE) was used to identify opacities and hypoplasia. Data were presented using descriptive statistics. Results: A high proportion (77.8%) had microcephaly, and 55.5% had low birth weight. Musculoskeletal disorders, swallowing difficulty, and self-injury practices were present in all children. Among the systemic findings, visual impairment (77.8%) and seizures (77.8%) were widely reported. Concerning disorders related to the stomatognathic system, bruxism (66.7%) and difficulty in sucking (33.3%) were present. For most children (77.8%), the deciduous right lower central incisor was the first tooth to erupt (minimum 8 months and maximum 17 months). Enamel defects were diagnosed in only two children (22.2%). Conclusion: A wide range of systemic manifestations was observed in children with CZS, including visual impairment and musculoskeletal disorders. Delayed eruption of the first deciduous tooth was also observed. Enamel defects were present in a small proportion of children.